Substrate coupling in digital circuits in mixed-signal smart-power systems. - Secareanu, R.M.
This paper describes theoretical and experimental data characterizing the sensitivity of nMOS and CMOS digital circuits to substrate coupling in mixed-signal, smart-power systems. The work presented here focuses on the noise effects created by high-power analog circuits and affecting sensitive digital circuits on the same integrated circuit. The sources and mechanism of the noise behavior of such digital circuits are identified and analyzed. The results are obtained primarily from a set of dedicated test circuits specifically designed, fabricated, and evaluated for this work. The conclusions drawn from the theoretical and experimental analyses are used to develop physical and circuit design techniques to mitigate the substrate noise problems. These results provide insight into the noise immunity of digital circuits with respect to substrate coupling.
Keywords: CMOS digital circuits; Circuit design techniques; Complementary metal-oxide-semiconductor.; High power analog circuits; Integrated circuit; Mixed signal smart power systems; nMOS digital circuits; Noise effects; Noise immunity; Sensitive digital circuits; Sensitivity; Substrate coupling; Test circuits